Model Nostalgic Emotion dalam Menciptakan Tourist Engagement - Setiawan, Rahyuniati; Hurriyati, Ratih; Wibowo, Lili Adi; Gaffar, Vanessa (Jurnal Ilmu Manajemen dan Bisnis, 2021)
The problem studied in this study is the decline in tourist visits to natural hot spring tourist destinations in West Java Province. Nostalgic emotion plays an important role in influencing tourist engagement and impacts memorable tourism experiences as intervening. This study aimed to determine the effect of nostalgic emotion on memorable tourism experience and impact on tourist engagement. The research subject is visitors in natural hot spring tourist destinations in West Java Province in this study. The method used in this research is an explanatory survey. Respondents in this study were visitors to the natural hot spring tourist destinations of West Java Province at the time of the study, amounting to 400 people. The sampling technique used in this research is proportional random sampling. This study uses a questionnaire as a data collection tool and data analysis techniques using SEM (Structural Equation Modeling) analysis using AMOS software version 20. The results show that nostalgic emotion has a positive influence on memorable tourism experiences. The results also show that memorable tourism experiences and nostalgic emotion impact on tourist engagement.